2009
DOI: 10.1007/s10719-009-9231-3
|View full text |Cite
|
Sign up to set email alerts
|

Novel mannosidase inhibitors probe glycoprotein degradation pathways in cells

Abstract: Multiple isoforms of mammalian alpha-mannosidases are active in the pathways of N-linked glycoprotein synthesis and catabolism. They differ in specificity, function and location within the cell and can be selectively inhibited by imino sugar monosaccharide mimics. Previously, a series of structurally related novel 7-membered iminocyclitols were synthesised and found to be inhibitors of alpha-mannosidase using in vitro assays. The present study aimed to delineate alpha-mannosidases hydrolytic pathways in azepan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Down-regulation of Man2C1-induced Apoptosis Is Independent of the Man2C1 ␣-Mannosidase Activity-Man2C1 is the ␣-mannosidase involved in the catabolic pathway that processes free oligosaccharides in the cytosol (5,7,8,15,17,40). We and others previously identified in vivo inhibitors of this enzyme (14,16). Interestingly, although we saw increased free oligosaccharides in the cytosol, we did not observe any cell growth defect in the presence of this inhibitor (16).…”
Section: Down-regulation Of Man2c1 By Shrna Induces Hela Cellmentioning
confidence: 49%
“…Down-regulation of Man2C1-induced Apoptosis Is Independent of the Man2C1 ␣-Mannosidase Activity-Man2C1 is the ␣-mannosidase involved in the catabolic pathway that processes free oligosaccharides in the cytosol (5,7,8,15,17,40). We and others previously identified in vivo inhibitors of this enzyme (14,16). Interestingly, although we saw increased free oligosaccharides in the cytosol, we did not observe any cell growth defect in the presence of this inhibitor (16).…”
Section: Down-regulation Of Man2c1 By Shrna Induces Hela Cellmentioning
confidence: 49%
“…Other authors concluded that kifunensine had affected ER mannosidase in their experimental conditions 90 . Different IC 50 of the latter are mentioned in the literature.…”
Section: High Mannose Speciesmentioning
confidence: 96%
“…Polyhydroxy substituted piperidine derivatives strongly and competitively inhibited the enzyme activity in a study of class II α-mannosidase from Aspergillus fischeri. N-butyl-azepane derivatives displayed a remarkable selectivity for the inhibition of cytosolic α-mannosidase in both HL60 and MDBK cells cultured in RPMI 1640 medium and led to a drastic increase of high mannose species at a concentration of 100 µM, showing substantial inhibition capability of these compounds 90 . More recently, the role of a plant-derived alkaloid called calystegine B 3 was studied both in vitro and in vivo.…”
Section: High Mannose Speciesmentioning
confidence: 99%
“…Swainsonine also possesses antimetastatic, anti-proliferative, and immunomodulatory properties [131]. Another mannosidase inhibitor is kifunensin, an alkaloid originally isolated from Kitasatosporia kifunense, which specifically inhibits α-mannosidase I [132]. In vitro studies showed that Kifunensine blocks the linkage of GlcNAc in N-glycans branches, which further prevents the effects of GlcNAc on neurogenesis of neural stem and progenitor cells (NSPC) [133].…”
Section: Glycan/glycoprotein Natural/semisynthetic Glycan Mimeticsmentioning
confidence: 99%